A Preliminary Study of White Matter in Adolescent Depression: Relationships with Illness Severity, Anhedonia, and Irritability - Henderson, Sarah E.; Johnson, Amy R.; Vallejo, Ana I.; Katz, Lev; Wong, Edmund; Gabbay, Vilma (Frontiers in Psychiatry, 2013)
Major depressive disorder (MDD) during adolescence is a common and disabling psychiatric condition; yet, little is known about its neurobiological underpinning. Evidence indicates that MDD in adults involves alterations in white and gray matter; however, sparse research has focused on adolescent MDD. Similarly, little research has accounted for the wide variability of symptom severity among depressed teens. Here we aimed to investigate white matter (WM) microstructure between seventeen adolescents with MDD compared to sixteen matched healthy controls (HC) using diffusion tensor imaging (DTI). We further assessed within the MDD group relationships between WM integrity and depression severity, as well as anhedonia and irritability—two core symptoms of adolescent MDD. As expected, adolescents with MDD manifested decreased WM integrity compared to HC in the anterior cingulum and anterior corona radiata. Within the MDD group, greater depression severity was correlated with reduced WM integrity in the genu of corpus callosum, anterior thalamic radiation, anterior cingulum, and sagittal stratum. However, anhedonia and irritability were associated with alterations in distinct WM tracts. Specifically, anhedonia was associated with disturbances in tracts related to reward processing, including the anterior limb of the internal capsule and projection fibers to the orbitofrontal cortex. Irritability was associated with decreased integrity in the sagittal stratum, anterior corona radiata, and tracts leading to prefrontal and temporal cortices. Overall, these preliminary findings provide further support for the hypotheses that there is a disconnect between prefrontal and limbic emotional regions in depression, and that specific clinical symptoms involve distinct alterations in WM tracts.